The Influence of Credit Risk, Liquidity Risk, Operational Risk, Market Risk and Solvency Risk on Profitability - Ahmad Ramadani (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2024)
This study aims to determine the extent of the influence of credit risk, liquidity risk, operational risk, market risk and solvency risk on the profitability of banks listed on the LQ45 index for the period 2018 - 2022. The type of research used is quantitative with causal associative methods. The data used is secondary data from the annual financial statements for the 2018-2022 fiscal year from the official website of the Indonesia Stock Exchange (IDX). The research sample was selected using purposive sampling technique so that 30 samples were obtained. The methods used include multiple regression analysis, t test, F test, and coefficient of determination. The results showed that X1_Non Performing Loan (NPL) had a negative and insignificant effect on Return On Asset (ROA), X2_Loan to Deposit Ratio (LDR) and X4_Net Interest Margin (NIM) had a significant positive effect on Return On Asset (ROA), X3_Operational Efficiency Ratio (OER) had a significant negative effect on Return On Asset (ROA), X5_Debt to Equity Ratio (DER) had a positive and insignificant effect on Return On Asset (ROA). And the five variables simultaneously have a significant effect on Return On Asset (ROA).